From Monoculture to Multiculture: a Critical Perspective on the Development of Pluralism in Education - Spajić-Vrkaš, Vedrana (2003)
The paper analyses critical points of the process of recognition of cultural differences and the acceptance of pluralism in educational theory, policy and practice. The impact of "scientific ideologies" on national educational policies and practices in this respect is analysed through two distinctive phases each comprising a set of different perspectives. In the pre-recognition phase three approaches are identified and described as the Golden Ages of Ignorance, the Disturbing Ages of Rhetoric and the Promising Ages of Accommodation. In the recognition phase three new approaches emerge depending on how the differences are conceptualised. Under the monocultural perspective, which is influenced by Social Darwinism and the doctrine of modernisation, the differences are seen as transitional quality and often described as social anomaly. The approach is reflected in education as the request for equal integration of culturally different children into the mainstream culture. In the multicultural perspective, which emerges through the acceptance of pluralism, the differences are seen as social reality. This view finds its place in education through cultural retention policies, often implemented in form of isolated, stereotyped and past-oriented minority programmes for which the term "ethnocentric multiculturalism" is coined. Finally, in the intercultural perspective the differences are seen as social strength, which means that it presupposes cultural dialogue and exchanges between and among different cultures. The author argues that the recognition of pluralism understood in terms of intercultural exchanges is still to be achieved.
Projekt MZOS
ENG